The Advances of Metal Sulfides and In Situ Characterization Methods beyond Li Ion Batteries: Sodium, Potassium, and Aluminum Ion Batteries. Issue 1 (19th November 2019) - Chen, Jingwei; Chua, Daniel H. C.; Lee, Pooi See
Abstract: With increasing cost and supply risks of lithium‐ion batteries (LIBs), exploitation of alternative metal‐ion batteries has been ongoing in recent years. Sodium‐ion batteries (SIBs), potassium‐ion batteries (PIBs), and aluminum‐ion batteries (AIBs) have unique advantages as post‐LIB alternatives. Nonetheless, development of electrode materials with high capacity, good reversibility, and extended cycling stability remains challenging. Metal sulfides (MSs), with improved electronic conductivity and better reversibility than metal oxide counterparts, as well as high theoretical capacities, are deemed as promising electrode materials and have been investigated in SIBs, PIBs, and AIBs. However, the cycling stability of MSs is still a persistent limitation. In order to manifest the advantages while overcoming the drawbacks of MSs, multiple strategies have been attempted. In this review, the approaches to improve the electrochemical performances of MSs in SIBs, PIBs, and AIBs, including nanostructuring and carbon incorporation, creation of hollow interiors, composition and crystal structures engineering, etc., are summarized and elaborated. Recent advances using in situ characterization methods to probe the complex electrochemical mechanisms of MSs in SIBs, PIBs, and AIBs are also presented and highlighted. The issues to be tackled are listed and the future directions for performance improvements of MSs in SIBs, PIBs, and AIBs are discussed. Abstract : Metal sulfides are promising electrode materials for sodium/potassium/aluminum ion batteries with high theoretical capacities, high electronic conductivity, and good reversibility, while their limited cycling stability remains a bottleneck. This review summarizes the effective structural and compositional approaches in improving the electrochemical performances of metal sulfides electrodes, and elaborates the recent advances in understanding electrochemical mechanisms of metal sulfides in sodium/potassium/aluminum ion batteries using in situ characterization methods.